Actinomycin D Inhibits Human Immunodeficiency Virus Type 1 Minus-Strand Transfer in In Vitro and Endogenous Reverse Transcriptase Assays - Guo, Jianhui (American Society for Microbiology, 1998)
In this report we demonstrate that human immunodeficiency virus type 1 (HIV-1) minus-strand transfer, assayed in vitro and in endogenous reactions, is greatly inhibited by actinomycin D. Previously we showed that HIV-1 nucleocapsid (NC) protein (a nucleic acid chaperone catalyzing nucleic acid rearrangements which lead to more thermodynamically stable conformations) dramatically stimulates HIV-1 minus-strand transfer by preventing TAR-dependent self-priming from minus-strand strong-stop DNA [(−) SSDNA]. Despite this potent activity, the addition of NC to in vitro reactions with actinomycin D results in only a modest increase in the 50% inhibitory concentration (IC(50)) for the drug. PCR analysis of HIV-1 endogenous reactions indicates that minus-strand transfer is inhibited by the drug with an IC(50) similar to that observed when NC is present in the in vitro system. Taken together, these results demonstrate that NC cannot overcome the inhibitory effect of actinomycin D on minus-strand transfer. Other experiments reveal that at actinomycin D concentrations which severely curtail minus-strand transfer, neither the synthesis of (−) SSDNA nor RNase H degradation of donor RNA is affected; however, the annealing of (−) SSDNA to acceptor RNA is significantly reduced. Thus, inhibition of the annealing reaction is responsible for actinomycin D-mediated inhibition of strand transfer. Since NC (but not reverse transcriptase) is required for efficient annealing, we conclude that actinomycin D inhibits minus-strand transfer by blocking the nucleic acid chaperone activity of NC. Our findings also suggest that actinomycin D, already approved for treatment of certain tumors, might be useful in combination therapy for AIDS.